I'll Always Come Back! - Metzger, Steve; Nang Chan Yeema (New York, USA Scholastic Inc., 2002)
Follows a child's day at school - from drop-off to pickup. Young children will be reassured to know that their loved ones always come back at the end of the school day.
Keywords: Story Collection